Triazine-cored polymeric vectors for antisense oligonucleotide delivery in vitro and in vivo - Wang, Mingxing (J Nanobiotechnology, 2020)
BACKGROUND: The polymer-based drug/gene delivery is promising for the treatment of inherent or acquire disease, because of the polymer’s structural flexibility, larger capacity for therapeutic agent, low host immunogenicity and less cost. Antisense therapy is an approach to fighting genetic disorders or infections using antisense oligonucleotides (AOs). Unfortunately, the naked AOs showed low therapeutic efficacy in vivo and in clinical trial due to their poor cellular uptake and fast clearance in bloodstream. In this study, a series of triazine-cored amphiphilic polymers (TAPs) were investigated for their potential to enhance delivery of AOs, 2′-O-methyl phosphorothioate RNA (2′-OMePS) and phosphorodiamidate morpholino oligomer (PMO) both in vitro and in vivo. RESULTS: TAPs significantly enhanced AO-induced exon-skipping in a GFP reporter-based myoblast and myotube culture system, and observed cytotoxicity of the TAPs were lower than Endoporter, Lipofectamine-2000 or PEI 25K. Application of optimized formulations of TAPs with AO targeted to dystrophin exon 23 demonstrated a significant increase in exon-skipping efficiency in dystrophic mdx mice. The best ones for PMO and 2′-OMePS delivery have reached to 11-, 15-fold compared with the AO only in mdx mice, respectively. CONCLUSION: The study of triazine-cored amphiphilic polymers for AO delivery in vitro and in mdx mice indicated that the carrier’s performances are related to the molecular size, compositions and hydrophilic-lipophilic balance (HLB) of the polymers, as well as the AO’s structure. Improved exon-skipping efficiency of AOs observed in vitro and in mdx mice accompanied with low cytotoxicity demonstrated TAP polymers are potentials as safe and effective delivery carrier for gene/drug delivery.